"Because if we talk about health issues first, it is easier to talk about human trafficking"; findings from a mixed methods study on health needs and service provision among migrant and trafficked fishermen in the Mekong - Nicola S. Pocock; Reena Tadee; Kanokwan Tharawan; Wansiri Rongrongmuang; Brett Dickson; Soksreymom Suos; Ligia Kiss; Cathy Zimmerman (BMC, 2018)
Abstract Background Human trafficking in the fishing industry or "sea slavery" in the Greater Mekong Subregion is reported to involve some of the most extreme forms of exploitation and abuse. A largely unregulated sector, commercial fishing boats operate in international waters far from shore and outside of national jurisdiction, where workers are commonly subjected to life-threatening risks. Yet, research on the health needs of trafficked fishermen is sparse. This paper describes abuses, occupational hazards, physical and mental health and post-trafficking well-being among a systematic consecutive sample of 275 trafficked fishermen using post-trafficking services in Thailand and Cambodia. These findings are complemented by qualitative interview data collected with 20 key informants working with fishermen or on issues related to their welfare in Thailand. Results Men and boys trafficked for fishing (aged 12-55) were mainly from Cambodia (n = 217) and Myanmar (n = 55). Common physical health problems included dizzy spells (30.2%), exhaustion (29.5%), headaches (28.4%) and memory problems (24.0%). Nearly one-third (29.1%) reported pain in three or more areas of their body and one-quarter (26.9%) reported being in "poor" health. Physical health symptoms were strongly associated with: severe violence; injuries; engagement in long-haul fishing; immigration detention or symptoms of mental health disorders. Survivors were exposed to multiple work hazards and were perceived as disposable when disabled by illness or injuries. Employers struggled to apply internationally recommended Personal Protective Equipment (PPE) practices in Thailand. Non-governmental organizations (NGOs) encountered challenges when trying to obtain healthcare for uninsured fishermen. Challenges included fee payment, service provision in native languages and officials siding with employers in disputes over treatment costs and accident compensation. Survivors' post-trafficking concerns included: money problems (75.9%); guilt and shame (33.5%); physical health (33.5%) and mental health (15.3%). Conclusion Fishermen in this region are exposed to very serious risks to their health and safety, and their illnesses and injuries often go untreated. Men who enter the fishing industry in Thailand, especially migrant workers, require safe working conditions and targeted protections from human trafficking. Survivors of the crime of sea slavery must be provided with the compensation they deserve and the care they need, especially psychological support.